2011
DOI: 10.1086/657667
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Capacity during an Influenza Pandemic—Buenos Aires, Argentina, 2009

Abstract: At a major referral hospital in the Southern Hemisphere, the 2009 influenza A (H1N1) pandemic brought increased critical care demand and more unscheduled nursing absences. Because of careful preparedness planning, including rapid expansion and redistribution of the numbers of available beds and staff, hospital surge capacity was not exceeded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Critically ill patients occasionally received mechanical ventilation outside the ICU, at the emergency department or special facilities [40], [41]. In most patients, ARDS with respiratory failure was the leading cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients occasionally received mechanical ventilation outside the ICU, at the emergency department or special facilities [40], [41]. In most patients, ARDS with respiratory failure was the leading cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…Following the PICOS framework, the characteristics of the 16 studies included in the narrative analysis are described in Table 2. The studies can be grouped into three categories: those focussing on a simulated influenza outbreak (eight articles, mostly published before 2011) [25][26][27][28][29][30][31][32] ; those assessing temporal effects of the H1N1 pandemic (three articles published between 2011 and 2015) [33][34][35] ; and those assessing effects at the early stages of the COVID-19 pandemic (five articles published in the first half of 2020). [36][37][38][39][40] Three-quarters (75%) of the retained articles covered high-income countries in Europe (five studies), North America (4), and Oceania (3); two (13%) studies covered upper-middle-income countries in South America; one (6%) covered a high-income economy in Asia; and one (6%) used a model population.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…33 Workforce planning involved the need to accommodate a national policy to furlough workers with high-risk medical conditions; in the study setting, data revealed that 6% of hospital nurses accepted six weeks of paid leave over three months. 33 While overall nursing absences were found to be similar to prepandemic periods, unscheduled absences increased, reaching a peak of 43% of nurses scheduled for duty on a given day. Nursing surge capacity was managed through temporary hiring, cancellation of vacations and other scheduled absences, and shifting to higher acuity care areas (given fewer hospitalized patients attributable to postponed surgeries).…”
Section: Factors Considered To Affect Hrh Surge Capacity During the H1n1 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…A key factor that may limit achieving this goal is the availability of ventilators, requiring anesthesia machines and regional stockpiles to be used. 41 Crisis care (200% beyond usual capacity or three times the usual ICU beds) will most likely require access to outside resources, such as strategic national stockpiles, and will likely require 48 to 72 h to achieve. Th e facility should identify what spaces would be used and what supplemental supplies (monitors, beds, and ventilators) would be required to minimize delays if occasion warrants.…”
mentioning
confidence: 99%